New data on one of the first plesiosaur (Reptilia, Sauropterygia) skeletons recovered from Antarctica, with comments on the dorsal and sacral regions of elasmosaurids - José P. O’Gorman (11403818); Franco Aspromonte (11403821); Marcelo Reguero (710203) (2021)
Elasmosaurids are among the most frequently recorded marine reptile fossils from the Campanian–Maastrichtian strata of Antarctica. Here, we describe one of the earliest quarried specimens, MLP 82-I-28-1, which is identified as a non-aristonectine elasmosaurid and phylogenetically nested within Weddellonectia. An ancestral states analysis of dorsal and sacral vertebral counts suggests that weddellonectian elasmosaurids plesiomorphically possessed between 17 and 18 dorsal vertebrae. The comparatively high count of 24 dorsal vertebrae observed in aristonectine elasmosaurids, such as Aristonectes quiriquinensis , thus likely represents a derived state correlated with the acquisition of larger body size. José O’Gorman [joseogorman@fcnym.unlp.edu.ar ] División Paleontología Vertebrados, Museo de La Plata, Universidad Nacional de La Plata, Paseo del Bosque s/n., B1900FWA La Plata; CONICET: Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina, Godoy Cruz 2290, C1425FQB, CABA, Argentina; Franco Aspromonte [fran.aspromonte@gmail.com ] División Paleontología Vertebrados, Museo de La Plata, Universidad Nacional de La Plata, Paseo del Bosque s/n., B1900FWA La Plata; Marcelo Reguero [mreguero@dna.gov.ar ] División Paleontología Vertebrados, Museo de La Plata, Universidad Nacional de La Plata, Paseo del Bosque s/n., B1900FWA La Plata; Instituto Antártico Argentino, 25 de Mayo 1143, B1650HMK, San Martín, Buenos Aires, Argentina.